2000
DOI: 10.1258/1357633001933952
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial to assess the clinical effectiveness of both realtime and store-and-forward teledermatology compared with conventional care

Abstract: The clinical effectiveness of realtime teledermatology, store-and-forward teledermatology and conventional outpatient dermatological care were evaluated in a randomized control trial. A total of 204 patients took part--102 patients were randomized to the realtime teledermatology consultation, 96 of whose cases were also referred using a store-and-forward technique, and 102 to the conventional outpatient consultation. There were no differences in the reported clinical outcomes of realtime teledermatology and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 7 publications
(6 reference statements)
1
30
1
1
Order By: Relevance
“…We assumed that the outcomes of the two alternatives were similar, based on previous research evidence. [5][6][7][8][9][10] We also included administrative costs, a variable seldom examined in previous research.…”
Section: Methodsmentioning
confidence: 99%
“…We assumed that the outcomes of the two alternatives were similar, based on previous research evidence. [5][6][7][8][9][10] We also included administrative costs, a variable seldom examined in previous research.…”
Section: Methodsmentioning
confidence: 99%
“…Historically, store-and-forward teletechnologies that transmit data, still images, or video recordings [5][6][7] have been used for providing consultative services and monitoring chronic-health conditions [8][9][10]. However, rehabilitation depends on real-time two-way observation, communication, and interaction between the therapist and the patient.…”
Section: Literature Review Teletechnologymentioning
confidence: 99%
“…It has also been shown that there are few differences in the type or complexity of cases referred for teledermatology or in-person consultation 5 . There is still some debate regarding the economic value of teledermatology, but as technology costs have continued to decrease and as more variables have been incorporated into the cost-benefit models, cost-savings have been noted [6][7][8][9] .…”
mentioning
confidence: 99%